Matematică
silviunaghel
2015-11-01 22:37:57
Sa se descompuna: a) 3x(x+5) + (x+5) + 7(x+5) b)(2x+1)(x+1)+5(2x+1)²-10x(2x+1) c)√2a(a-b)+√2b(a-b)-√2(b-a)
Răspunsuri la întrebare
dobircianuandr
2015-11-02 02:09:53

a)3x(x+5)+x+5+7(x+5)=(3x)(x)+(3x)(5)+x+5+(7)(x)+(7) =3x²+15x+x+5+7x+35=3x²+15x+x+5+7x+35=(3x²)+(15x+x+7x)+(5+35) =3x²+23x+40 b)(2x+1)(x+1)+5(2x+1)²-10x(2x+1)=(2x)(x)+(2x)(1)+(1)(x)+(1)(1)+20x²+20x+5+−20x²+−10x=2x²+2x+x+1+20x²+20x+5+−20x²+−10x=2x²+2x+x+1+20x²+20x+5+−20x²+−10x=(2x²+20x²+−20x²)+(2x+x+20x+−10x)+(1+5)=2x²+13x+6 c)√2a(a-b)+√2b(a-b)-√2(b-a)=1.414214a²−1.414214b²+1.414214a−1.414214b

Adăugați un răspuns